Appendiceal orifice inflammation is associated with proximal extension of disease in patients with ulcerative colitis. (2nd August 2016) - Anzai, H.; Hata, K.; Kishikawa, J.; Ishii, H.; Yasuda, K.; Otani, K.; Nishikawa, T.; Tanaka, T.; Kiyomatsu, T.; Kawai, K.; Nozawa, H.; Kazama, S.; et al.
Abstract: Aim: Ulcerative colitis (UC) is considered to be a disease of continuous mucosal inflammation extending proximally from the rectum. However, appendiceal orifice inflammation (AOI) is a skip lesion with segments of continuous involvement from the rectum. The aim of this study was to examine the clinical characteristics and clinical course, particularly focused on proximal extension, of UC in patients with AOI. Method: A retrospective evaluation of patients with UC who underwent total colonoscopy at the Department of Surgical Oncology, The University of Tokyo, from 2004 to 2014. The degree of AOI was graded endoscopically as follows: 0 (no inflammation); 1 (slight oedema); 2 (moderate inflammation); and 3 (marked inflammation). A total of 189 patient records were reviewed retrospectively. The presence of AOI was analysed with regard to the clinical information of each patient, and its association with proximal extension of proctitis or left‐sided colitis was evaluated. Results: Of 189 patients with UC who underwent total colonoscopy at our institution, 92 were diagnosed with pancolitis, 50 with left‐sided colitis and 47 with proctitis. Endoscopic findings of AOI were observed in 26 patients, including 11 (12.0%) with pancolitis, six (12.0%) with left‐sided colitis and nine (19.1%) with proctitis. During follow up, proximal extension of the disease occurred in all nine patients with proctitis AOI. Conclusion: AOI is more frequently observed in patients with proctitis. Our results showed correlations between AOI and subsequent proximal extension of mucosal inflammation in patients with proctitis.